Recent Developments in Photocatalytic Reduction of Nitro Compounds to Valuable Scaffolds - Aggarwal, Varun; Bala, Ekta; Saima, Saima; Pathan, Sameer; Guleria, Saksham; Sharma, Sakshi; Selvaraj, Manickam; Verma, Praveen Kumar (Synlett, 2023)
The reduction of nitro compounds is one of the fundamental organic transformations and ascertain wide applicability in industrial chemistry, synthesis of valuable scaffolds, fine chemical synthesis, as well as environmental applicability for decontamination process. The transformation involves the conversion of nitro compounds into valuable scaffolds including amino, nitroso, hydroxyl amines, azo, and hydrazo compounds. Conventional approaches for the reduction of nitro compounds involves the environmentally harmful stoichiometric reagents, high-boiling reaction media, tedious processes, and harsh reaction conditions with high temperature and pressure. Additionally, the selectivity always remains a serious concern associated with the process due to the possibilities of several stable intermediate formation in the reaction pathway of reduction of nitro compounds. Nitro compounds are also of serious environmental concerns being a part of most harmful and high-priority classes of pollutants mainly released from industrial effluents, agricultural waste, and human sewage. A simple degradation of these pollutants bearing nitro group just removes the pollutants, however, the selective reduction of nitro group to valuable functionalities as mentioned above provides the industrially important scaffolds. With the advent of photocatalytic organic transformation, most of the scientific fraternity working in the area of organic synthesis, catalysis, and environmental decontaminations are utilizing the clean, green, low-temperature, energy and cost-effective, sustainable processes for the reduction of nitro compounds to access valuable scaffolds. Nowadays a lot of mechanistic developments in the field ease the processes for the developments of such highly valuable organic transformations. Herein, the present Account is focused on the recent developments in the photocatalytic reduction of nitro compounds to valuable scaffolds.1 Introduction2 Reduction of Nitro Compounds2.1 Conventional Approaches for Reduction of Nitro Compounds2.2 General Photocatalytic Mechanism3 Mechanistic Pathways: Electrochemical, Conventional and Photocatalytic Approaches3.1 Mechanism of Electrochemical Reduction of Nitroarene3.2 Conventional Reduction Mechanism of Nitroarenes3.3 General Photocatalytic Reduction Mechanism of Nitroarenes4 Photocatalytic Reduction of Nitro Compounds to Valuable Scaffolds4.1 Reduction of Nitro Compounds to Corresponding Amines4.2 Reduction of Nitro Compounds to Azo Compounds4.3 Reduction of Nitro Compounds to Azoxy Compounds4.4 Reduction of Nitro Compounds to Nitroso Compounds4.5 Reduction of Nitro Compounds to Hydroxyl Amines5 Future Perspective6 Conclusion
Keywords: amines; azo compounds; photochemistry; reduction; hydrogen transfer; hydrogenation; catalysis